Factores asociados a artritis séptica en los pacientes hospitalizados en el Área de Traumatología y Ortopedia del Hospital Isidro Ayora de la ciudad de Loja, en el periodo julio-diciembre del 2015. - Aguirre Campoverde, Erika Gabriela (2016)
This retrospective, descriptive research contains information relating to the factors associated with septic arthritis, obtained from the medical records of hospitalized patients in the Traumatology and Orthopedic unit of the 'Isidro Ayora de Loja' hospital in the city of Loja during the period July to December 2015. Out of a total of 275 patients admitted to the trauma unit, 32 met the criteria of septic arthritis. Septic arthritis is an acute articular inflammatory process due to the invasion and multiplication of pyogenic microorganisms in particular joints, caused by trauma, surgery or by multiple associated factors that can trigger this disease which affects children and the elderly in particular (Dr. Jaime Pedraza. Septic Arthritis 2002). Within the study population of 32 patients, it was determined that the average age in which septic arthritis occurs is 51-60 years old and 61 to 70 years old of which 56.2% are men and 43.75% women. The most commonly affected joint is the knee with 31.25%, followed by the hip with 28.12% and with a lower percentage of 6.25% the wrist. The most common predisposing factor is prior trauma with 68.75% with a comorbidity of diabetes mellitus with 15.62%. In addition it was determined that the main causal agent was Staphylococcus Aureus with 87.5%, of which 40.62% received antibiotic therapy and 59.37% surgical cleaning plus antibiotic therapy. Keywords: Degenerative joint disease, previous trauma, surgical cleaning, retrospective.